Diffuse Axonal Injury: Epidemiology, Outcome and Associated Risk Factors - Vieira, Rita de Cássia Almeida; Paiva, Wellingson Silva; de Oliveira, Daniel Vieira; Teixeira, Manoel Jacobsen; de Andrade, Almir Ferreira; Sousa, Regina Márcia Cardoso de (Frontiers in Neurology, 2016)
Abstract Diffuse axonal injury (DAI), a type of traumatic injury, is known for its severe consequences. However, there are few studies describing the outcomes of DAI and the risk factors associated with it. This study aimed to describe the outcome for patients with a primary diagnosis of DAI six months after trauma and to identify sociodemographic and clinical factors associated with mortality and dependence at this time point. Seventy-eight patients with DAI were recruited from July 2013 to February 2014 in a prospective cohort study. Patient outcome was analyzed using the Extended Glasgow Outcome Scale (GOS-E) within six months of the traumatic injury. The mean Injury Severity Score was 35.0 (SD = 11.9), and the mean New Injury Severity Score (NISS) was 46.2 (SD = 15.9). Mild DAI was observed in 44.9% of the patients and severe DAI in 35.9%. Six months after trauma, 30.8% of the patients had died, and 45.1% had shown full recovery according to the GOS-E. In the logistic regression model, the severity variables—DAI with hypoxia, as measured by peripheral oxygen saturation, and hypotension with NISS value—had a statistically significant association with patient mortality; on the other hand, severity of DAI and length of hospital stay were the only significant predictors for dependence. Therefore, severity of DAI emerged as a risk factor for both mortality and dependence.